Integration of wind and solar energies with battery energy storage systems into 36-zone Great Britain power system for frequency regulation studies - Rasoul Azizipanah-Abarghooee; Mostafa Malekpour; Mazaher Karimi; Vladimir Terzija (International Journal of Electrical Power & Energy Systems)
Variable-speed wind generators (VSWGs) and solar Photovoltaic (PV) units are being broadly employed as the main renewable energy sources in large-scale transmission power networks. However, they can cause system stability challenges following power imbalances since they provide no inertial and governor responses. In this study, generic dynamic models are developed for VSWGs, PVs and battery energy storages systems (BESSs) which include inertia emulator and droop-based frequency control schemes. These models are suitable for transmission systems stability studies and are integrated into 36-zone Great Britain (GB) power system in DIgSILENT PowerFactory. It is a very useful benchmark for academic research and industrial sectors to undertake feasibility studies for renewable energy integration into GB power system. However, it is not an exact equivalent of the real GB power system. The dynamic time-domain simulations and modal analysis are provided and justified to investigate how PV, Wind and BESS units affect the system frequency response. A sensitivity analysis is also carried out against several factors to demonstrate the dynamic performance of the test system incorporating the generic models for VSWGs, PVs and BESSs. These are associated with units’ frequency response and system frequency changes under renewable energies’ penetration levels of 20 %, 25 %, 50 %, 60 % and 75 % of system demand.